CUSTOMER SATISFACTION OF KERALA GRAMIN BANK IN ERNAKULAM DISTRICT, KERALA (International Journal of Food and Nutritional Sciences, 2022)
Indian economic expansion has been boosted by the country's improved financial infrastructure. The ultimate consumers of banks are the recipients of the services they provide. Following the liberalisation of the Indian economy in the 1990s, the banking industry underwent significant transformation. One of the most important factors in a bank's long-term success is the level of happiness its customers express. As the primary source of finance in rural areas, Regional Rural Banks are responsible for providing a wide range of agricultural loan products. The Kerala countryside is served by Kerala Gramin Bank (KGB), the state's sole rural regional bank. Kerala Gramin Bank improves performance and makes a profit of 124.14 crore in the last financial year. It was roughly four times compared to the profit of 33.43 crore that the bank made in the previous year. KGB, like many rural banks, is under competition from larger, more well-established banks in both the public and private sectors. For banks, keeping their customers happy is a constant battle. The purpose of this research was to analyse how happy Ernakulam, Kerala, customers are with Kerala Gramin Bank. The study relied on primary data from a sample of 200 consumers who filled out a questionnaire based on the one created by Mihelis et al., (2001). Z-test and analysis of variance (ANOVA) were employed for the analysis. According to the data, customers of Kerala Gramin bank are generally satisfied. In addition, we discovered that consumer satisfaction is quite stable across all of the demographic categories examined.